DETERMINANT FACTORS OF HOTEL EMPLOYEE PERFORMANCE IN BALI WITH THE MODERATOR OF ENVIRONMENTAL TURBULENCE - Halim, Linda; Handoyo, Sarwo Edy (International Journal of Application on Economics and Business, 2024)
The success of hotels in Bali is inseparable from the role of human resources in it. Therefore, the success of the hotel will be seen from the performance of employees in the hotel. Employee performance is determined by various aspects, one of which is leadership style, organizational commitment and quality of work life of the employees themselves as well as environmental turbulence factors. This study aims to look at the factors that affect the performance of hotel employees in Bali. This study uses quantitative research methods and was conducted in Bali with the research subjects of PT CWP employees in Bali. Research data based on primary data sources, namely through distribution using a questionnaire based on 5 variables to be measured, namely employee performance, entrepreneurial leadership, organizational commitment, and employee quality of life and environmental turbulence. The research population that will be the source of research data is PT CWP employees in Bali consisting of around 276 people. From this population, a research sample of 159 people was taken based on the simple random sampling method, the analysis method using SPSS Statistics 29. The results showed that entrepreneurial leadership, organizational commitment, and quality of employee life are positively and significantly related to employee performance moderated by environmental turbulence.